Renewable energy in Argentina: Energy policy analysis and perspectives - Recalde, Marina Yesica (2008)
This paper presents a brief analysis of the key points for the development of renewable energy. The aim was try to respond about two important questions: Can deployment of renewable energy put downward pressure on Argentinean supply system? If so, How could it be done? We found that majority of countries with high contribution of renewable energy in their supply have promoted them through energy policies. Nonetheless, Argentina has recently started to develop new promoting legislation, and the results have not been good enough. We conclude that, in order to get better results, the Government should increase and improve policies related to renewable energy.